Professional factors supporting workaholism among Tunisian engineers - A. Bouaziz; R. Sallemi; M. Bouhamed; R. Masmoudi; I. Feki; J. Masmoudi (European Psychiatry, 2022)
Introduction Workaholism or work addiction is a growing public health that may induce negative consequences on professional life. Engineers are at risk given the globalization and increased competition in their jobs.